A wolf in sheep's clothing: Dogs confer an unrecognized risk for their immunocompromised master. (2022) - Agarwal, Lipisha; Singh, Harpreet; Jani, Chinmay; Banankhah, Peymaan; Abdalla, Mohammed; Kurman, Jonathan S.; Franco, Rose A.
Abstract: Bordetella bronchiseptica is a pleomorphic gram-negative coccobacillus that commonly causes respiratory tract infections in canines, felines, and swine. Human infections are rare. We report a case of Bordetella bronchiseptica pneumonia in a 67-year-old immunocompromised host. His past medical history included multiple myeloma treated with autologous bone marrow transplant followed by a chimeric antigen receptor cell therapy for relapse. He was admitted with unrelenting diarrhea due to HHV-6 pancolitis. During the hospital course he developed high-grade fever (102.3°F), cough and respiratory failure requiring mechanical ventilation. Chest imaging demonstrated bilateral opacities most pronounced at lung bases and worsening mediastinal lymphadenopathy. Bronchoalveolar lavage cultures grew Bordetella bronchiseptica. He was treated with piperacillin/tazobactam, but developed progressive multiorgan failure, transitioned to comfort care, and expired in the hospital. Bordetella bronchiseptica is an organism that do not cause serious infection in immunocompetent persons but can sometimes cause serious illness in immunocompromised populations. It causes "kennel cough" in dogs and spready by respiratory droplets. Dogs and cats are not uniformly vaccinated against this pathogen. Therefore, transmission through animal contact is becoming increasingly common. Realize that unlike other Bordetella spp, this pathogen is not typically responsive to erythromycin and is often resistant to ampicillin and cephalosporins so the typical neutropenic fever coverage with an antipseudomonal cephalosporin and azithromycin might not be effective. Given the increasing recognition of this zoonosis as a threat to the immunocompromised, it is essential to educate immunocompromised patients to minimize zoonotic exposure, as immunization of pets might not confer protection to humans.